Expanded Therapeutic Applications of Holarrhena Antidysenterica: A Review - Tiwari, Ruchi; Khatri, Charul; Tyagi, Lalit K.; Tiwari, Gaurav (Combinatorial Chemistry & High Throughput Screening, 2024)
Background: The use of medicinal plants as a rich resource of therapeutic agents in the treatment and prevention of diseases & ailments has been recognized for millennia and is highly regarded worldwide. Holarrhena antidysenterica (H. antidysenterica), also called kurchi, or kutaj, has been utilized since the dawn of time, Apocynaceae member, also known as H. pubescens, is praised for the medicinal uses of its stem bark, leaves, and seeds in Ayurveda. Objective: The study concentrated on aggregate information regarding H. antidysenterica's therapeutic effects. The purpose of the study was to compile pharmacological activities of H. antidysentrica seeds. Methods: Regardless of its broad variety of biological and possible therapeutic uses, there has been increasing concern regarding the use of H. antidysenterica. Result: Various phytochemicals have been extracted from H. antidysenterica in recent years and have demonstrated typical pharmacological properties, including antibacterial, anti-diarrhoeal, anti-diabetic, anti-oxidant, anti-urolithic, and anti-inflammatory activity. Conclusion: This review paper investigated the in-depth description and pharmacological properties of the plant, which produced significant findings on the chemical components present and also verified the traditionally claimed properties associated with the plant.
Keywords: anti-diarrheal activity